2019
DOI: 10.1155/2019/3151823
|View full text |Cite
|
Sign up to set email alerts
|

Compilation and Application of UMAT for Mechanical Properties of Heterogeneous Metal Welded Joints in Nuclear Power Materials

Abstract: For the problem of mechanical properties of heterogeneous dissimilar metal welded joints, when analyzed by the finite element method, it is usually simplified into a “sandwich” material structure model. However, the mechanical properties of materials in different regions of the “sandwich” material mechanics model are different, and there will be mutations at the material interface. In order to accurately describe the mechanical properties of welded joints, the constitutive equations of dissimilar metal welded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…e accuracy and reliability of the subroutine are verified by numerical simulation and experiment. Xue et al [19] have established the continuous transition model of the welded joint based on the User-Defined Material Mechanical Behavior (UMAT) subroutine in the ABAQUS and found that the stress field at the crack tip of the continuous transition model deflects to the low yield strength zone. However, the writing progress of UMAT subroutines is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…e accuracy and reliability of the subroutine are verified by numerical simulation and experiment. Xue et al [19] have established the continuous transition model of the welded joint based on the User-Defined Material Mechanical Behavior (UMAT) subroutine in the ABAQUS and found that the stress field at the crack tip of the continuous transition model deflects to the low yield strength zone. However, the writing progress of UMAT subroutines is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…A sudden change in the mechanical properties at the material interface is produced, and it cannot accurately describe the mechanical heterogeneity of the DMWJ. us, structural integrity assessment has certain limitations by using the "Sandwich" model [15][16][17]. More detailed characterization of the DWMJ mechanical properties will greatly help the research of the crack tip mechanical field.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the mechanical field and driving force at the tip of SCC in different positions of the welded joint are analyzed by the "Sandwich" model has been unable to meet the requirements [20][21][22]. To characterize the distribution of mechanical properties in the DMWJ more accurately, some scholars [23,24] tried to use some subroutines in ABAQUS to realize the uneven distribution of mechanical properties varies along with the spatial position. Xue et al [23] have established the "Sandwich" model and the heterogeneous material model of the DMWJ based on the user-defined field (USDFLD) subroutine, and the results illustrate that the heterogeneous material model compensated for the sudden change of the mechanical properties of the Sandwich model at the interface.…”
Section: Introductionmentioning
confidence: 99%